Kinetic acetylation of hydroxyl groups of isoprene copolymer and hydroxyethyl methacrylate - Бойко, Виталий Петрович (Technology audit and production reserves, 2014)
Using the method of kinetic acetylation (MKA) for the differentiation of the hydroxyl groups in oligomers is considered and some results of our research in this field are given in the paper. The main purpose of the research is to describe the method of acetylation of the hydroxyl groups and calculate kinetic parameters, as well as using the method for analyzing isoprene copolymer and hydroxyethyl methacrylate obtained by polymerization using hydrogen peroxide as the initiator. The reaction capacity differentiation of the hydroxyl groups is important either for obtaining polymer materials according to the reactions of the hydroxyl groups (HG), or understanding the mechanisms of polymerization. The obtained results allowed to reveal that the copolymer contains two types of hydroxyl groups, differing by the reaction capacity. More active HG are arranged at the molecules ends and introduced by hydroxyl radicals, initiating the polymerization, and less active are located in the polymer chain and introduced by the MEG molecules. It was found that a number of more active groups are below 2 per molecule, indicating that the chain is branching. The research results can be used in chemistry for studying hydroxyl oligomers to obtain polymer materials, in particular, in the preparation of polyurethanes.